Diversification Slowdown in the Cirrhopetalum Alliance (Bulbophyllum, Orchidaceae): Insights From the Evolutionary Dynamics of Crassulacean Acid Metabolism - Hu, Ai-Qun; Gale, Stephan W.; Liu, Zhong-Jian; Fischer, Gunter A.; Saunders, Richard M. K. (Frontiers in Plant Science, 2022)
Evolutionary slowdowns in diversification have been inferred in various plant and animal lineages. Investigation based on diversification models integrated with environmental factors and key characters could provide critical insights into this diversification trend. We evaluate diversification rates in the Cirrhopetalum alliance (Bulbophyllum, Orchidaceae subfam. Epidendroideae) using a time-calibrated phylogeny and assess the role of Crassulacean acid metabolism (CAM) as a hypothesised key innovation promoting the spectacular diversity of orchids, especially those with an epiphytic habit. An explosive early speciation in the Cirrhopetalum alliance is evident, with the origin of CAM providing a short-term advantage under the low atmospheric CO2 concentrations (pCO2) associated with cooling and aridification in the late Miocene. A subsequent slowdown of diversification in the Cirrhopetalum alliance is possibly explained by a failure to keep pace with pCO2 dynamics. We further demonstrate that extinction rates in CAM lineages are ten times higher than those of C3 lineages, with CAM not as evolutionarily labile as previously assumed. These results challenge the role of CAM as a ‘key innovation’ in the diversification of epiphytic orchids.